MARKETING STRATEGY OF A UNIVERSITY: THE «7P» SYSTEM - Malynka, Oksana (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
This article describes the model of a university as an open system influenced by the factors of the marketing environment. Based on the systemic approach, the concept of the «7Ps» as a part of the marketing system is highlighted, and its application to the development of the marketing strategy of a university is explained.